PENGARUH PH TERHADAP NILAI VOLATILE FATTY ACID (VFA) LATEKS PEKAT - Syafrinal Syafrinal; Melysa Putri; Yosi Amelia Putri (Politeknik ATI Padang, 2022)
One of the factors that affect the quality of concentrated latex is pH. The purpose of this study was to determine the effect of pH on the value of Volatile Fatty Acid (VFA) of concentrated latex. The method used is titration using Ba(OH)2 as the titrant and BTB as an indicator. The results showed that the pH of the initial concentrated latex pH 10 the VFA value was 0.0158%. Then on decreasing the pH at pH 9.50 the VFA value was 0.0219%, at pH 9 the VFA value was 0.0328% and at pH 8.5 the VFA value was 0.0522%. However, at pH 10.5 which the pH was increased from the initial conditions, the VFA value was 0.0129%. This shows that the lower the pH, the value of the Volatile Fatty Acid of concentrated latex increases, while if the pH is increased, the value of the Volatile Fatty Acid of concentrated latex decreases. A good pH condition for concentrated latex according to the American Society for Testing and Materials Standard (ASTM D.1076. Y80) with a maximum standard of 0.030% is at pH 9.5 - 10.5.